2018
DOI: 10.4085/1302131
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Impede and Promote the Persistence of Black Women in Athletic Training Programs

Abstract: Context: Black women are dramatically underrepresented in the health care profession of athletic training. The research identifies impeding barriers such as racism, sexism, lack of support, and unpreparedness to the successful college completion of ethnically diverse students. However, there are black women who have successfully overcome those impeding barriers to become athletic trainers (ATs). Mentoring is one factor that has been identified as supportive to the retention of ethnically dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…Certain personality traits or characteristics facilitated leadership by attracting women from culturally diverse backgrounds to become and continue as leaders in sport (n = 9). These included confidence (McDowell & Carter-Francique, 2017), determination (Armstrong, 2007; Siple et al, 2018), self-motivation (Siple et al, 2018), focus (Armstrong, 2007), hard work ethic (Rankin-Wright et al, 2019) and a caring nature (Armstrong, 2007). Confidence and career potential were impacted by discriminatory experiences; however, maturity offered a stance of accepting reality (e.g., “you can’t please everybody”; McDowell & Carter-Francique, 2017, pg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain personality traits or characteristics facilitated leadership by attracting women from culturally diverse backgrounds to become and continue as leaders in sport (n = 9). These included confidence (McDowell & Carter-Francique, 2017), determination (Armstrong, 2007; Siple et al, 2018), self-motivation (Siple et al, 2018), focus (Armstrong, 2007), hard work ethic (Rankin-Wright et al, 2019) and a caring nature (Armstrong, 2007). Confidence and career potential were impacted by discriminatory experiences; however, maturity offered a stance of accepting reality (e.g., “you can’t please everybody”; McDowell & Carter-Francique, 2017, pg.…”
Section: Resultsmentioning
confidence: 99%
“…Women also used previous experience to their advantage (n = 5). Specifically, prior experience interacting with predominantly white cultures armoured women with coping skills to manage in similar settings, including sport (Siple et al, 2018). Prior athletic careers also facilitated career progression, self-worth, confidence and social skills (Larsen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…There is little research that investigates the role of cross-cultural mentorship in athletic training, with most being focused on black women. 28,29 Cross-cultural mentoring involves an ongoing, intentional, and mutually enriching relationship with someone of a different race, gender, ethnicity, religion, cultural background, socioeconomic background, sexual orientation, or nationality. 30 In athletic training education, there will be students who fit every trait listed, but they may find that they do not have anyone who they can look toward who has the same background.…”
Section: Mentorshipmentioning
confidence: 99%
“…[6][7][8][9][10] These studies found that there are numerous reasons that may contribute to the lack of diversity in the health care workforce, including the lack of racially diverse people's access to higher education, institutionalized racism, financial instability, and an absence of mentoring. [6][7][8][9][10] A study that focused on black women in athletic training found that a lack of financial support and the presence of sexism and racism within the institution, classroom, and clinical sites were all factors that could negatively affect a minoritized student's ability to matriculate through athletic training education. 9 Research on diversity in nursing education programs found that minoritized students graduate at higher rates when they are provided with mentorship programs, tutoring, goal setting, financial support, and structured accountability.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] A study that focused on black women in athletic training found that a lack of financial support and the presence of sexism and racism within the institution, classroom, and clinical sites were all factors that could negatively affect a minoritized student's ability to matriculate through athletic training education. 9 Research on diversity in nursing education programs found that minoritized students graduate at higher rates when they are provided with mentorship programs, tutoring, goal setting, financial support, and structured accountability. 7,10 However, a study that focuses on recruitment and retention strategies aimed at minoritized students in athletic training education has yet to be completed.…”
Section: Introductionmentioning
confidence: 99%